answersLogoWhite

0


Best Answer

(2a-3)(a-1)

User Avatar

Wiki User

โˆ™ 2009-10-29 19:49:40
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: Factor the following polynomials 2a2 - 5a plus 3?
Write your answer...
Submit
Related questions

What is the other factor of 2a2 plus 5a plus 12?

The other factor is 1.


2a2 - 5a plus 3 factor the following polynomials?

Multiply the first and last coefficients.2*3=6What two factors give you six but when combined give you -5-2 and -3Therefore2x-3)(x-1) will be the factored model.


What is the complete factor form of 2a2 plus a?

a(2a + 1)


How do you factor 2a2-11a plus 5?

(2a - 1)(a - 5)


How do you factor 2a2 plus 2a minus 84?

2(a + 7)(a - 6)


What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)?

What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)


Simplify 3a4-2a2 plus 5a-10 - 2a4 plus 4a2 plus 5a-2 equals?

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)


Factor the polynomial 2a4 - 21a3 plus 49a2?

a2(2a2-21a+49) a2(2a-7)(a-7)


What is 2a2-13a plus 15 equal when factored?

2a2 - 13a + 15 = (2a - 3) (a - 5)


What does a squared plus a squared equal?

a2 + a2 = 2a2


Factor 2a2 - 5a 3?

(a - 1)(2a - 3)


25a5 plus 15a4 plus 10a3 divide 5a?

5a4 + 3a3 + 2a2


Factor a3 - 2a2 4a - 8?

(a - 2)(a^2 + 4)


A3 - 2a2 plus 4a - 8?

a3 - 2a2 + 4a - 8 = a2(a - 2) + 4(a - 2) = (a - 2)(a2 + 4)


What is a squared plus a plus a aquared?

(a2 + a + a2) = (2a2 + a) = a (2a + 1)


What is the factor of a3 - 2a2 plus 4a - 8?

First you can factor a^2 from the first two terms and 4 from the last two terms. (a^2)(a-2)+4(a-2) You can see that they both have (a-2) as a factor. So it is (a^2+4)(a-2)


What is 2a to the power of 2 plus 3a to the power of 2?

2a2+3a2 = 5a2


How do you factorize 2asquared plus a - 6?

8


What is 5a3-45a equals -2a2 plus 18?

5a3-45a=-2a2+18 5a(a2-9)=-2(a2-9) 5a=-2 a=-2/5


What is 2a2-46a plus 2520?

It is a quadratic expression which can't be factored because its discriminant is less than zero.


What is 2a x a?

2a2


Twice the square of a increased by the square of two a?

2a2+2a2 = 4a2


What is the square root of a squared plus a squared equal?

sqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*a


What should be subtracted from a2 -4a2 plus 5a2-6 to obatain a2-2a plus 1?

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7


What is the factored form of 2a2 33a 136?

2a2+33a+136 = (2a+17)(a+8) when factored